Analysis of prestressed concrete beam with small circular web opening by using ansys - Ming, Zhong (2014)
The provision of transverse openings in prestressed concrete beams of floor to facilitate the passage of utility pipes and service ducts results not only in a more systematic layout of pipes and ducts, it also translates into substantial economic savings in the construction of a multi-storey building, increase the usable area of building. In this thesis, to investigate the problem of openings in beams, choose small circular opening as consideration. By using manual calculation and personal computer software (ANSYS) to analysis the beam behaviours under point loads. The aspects will analyse the beam with opening through four input variables which are the density of prestressed cable, modulus of elasticity, point load 1 and point load 2, and then gain the output of parameters. The results include general situations of stress, strain, and deflection. Base on the past research and experimental test of literature, conclude manual results getting from software calculation, analysis the characteristics and the behaviours of the prestressed concrete beam with small circular opening. The objective of this project is based on the four input variables which are point load 1, point load 2, modulus of elasticity, and density of prestressed cable, to gain the three output parameters which are maximum deflection, maximum stress, and maximum strain. The statistic for the random input variables and output parameters had been computed by using the ANSYS software and illustrate the properties of the output parameters using histogram plots, cumulative distribution curves, and history plots. The influence of random input variables on the individual output parameters. Hence, the analysis was success and results collected were accurate and fit into use.